Payment for Environmental Services in the Sarapiquíy Toro Basins: Theoretical and Technical Implications from a Feasibility Analysis - Fallas, Agustín (2010)
This paper presents some theoretical and technical conclusions on the contribution of Forest Ecosystem Services to the reduction of deforestation rates in highly vulnerable areas of the Costa Rican Central Mountain Range and to the regulation of watersheds, and the resulting increased profitability of investments in hydro-electrical power plants. Particularly, the paper presents and applies a model to estimate different internal rates of return for investments in hydro-electrical power plants based on different percentages of Forest Ecosystem Services payment in the Sarapiquí and Toro watersheds where the Costa Rican public utility company Ice was building two hydro plants at the time of the study.